Pelatihan Teknik Proyeksi Bisnis Pada Kelompok Usaha Batu Bata Di Kelurahan Limbung Kecamatan Bajeng Kabupaten Gowa - Zainal Ruma; Romansyah Sahabuddin; Hety Budiyanti; Dwi Anugrah Lestari Musa; Anwar Anwar; Nurman Nurman (Pusat Riset dan Inovasi Nasional, 2023)
Community Service Partners (PKM) is a micro and small brick business. Knowledge of business projections among business owners in Batu Bata is still very limited. The aim of this service is to empower traditional business owners with the knowledge and skills to produce accurate business projections to assist in developing their business. The implementation method uses lecture, exercise, and discussion/question and answer methods. The participants were brick business owners from the Limbung village, Bajeng District, Gowa Regency. The technique for implementing this activity includes three stages starting from the preparation stage, implementation stage and activity evaluation stage. The results of the training show that traditional business owners experience difficulties in applying business forecasting techniques to their businesses because sales records are sometimes incomplete or non-existent. After carrying out the simulation, participants can understand the basis of sales forecasts for future sales forecasts. Additionally, brick-and-mortar business owners can know the exact estimates of their business. Knowledge of business forecasting is expected to improve business performance and competitiveness. The limitation of this training is that the implementation method does not use instructional techniques so that knowledge about business forecasting can be implemented in business activities.